The physiological role of polycomb group protein Ezh2 in dendritic cells - Loh, Jia Tong (2016)
The contribution of epigenetics in the regulation of leukocyte development and functions has gained increasing attention over the past years. Polycomb group protein Enhancer of Zeste homolog 2 (Ezh2) is a histone methyltransferase which regulates gene expression through the modification of chromatin structure via the addition of H3K27me3 marks. In this study, we aim to characterize the role of Ezh2 using Langerhans cells (LCs) and thymic dendritic cells (DCs) as model systems, and further elucidate the molecular mechanism and in vivo relevance underlying such regulation. Surprisingly, the well-established epigenetic repressor Ezh2 was found to control LC integrin-dependent migration via an epigenetic-independent mechanism involving the direct methylation of an extra-nuclear substrate Talin1. Deficiency in Ezh2 impairs the disassembly of adhesion structures which enhances the adhesive properties of LCs, leading to their reduced transmigration across the skin basement membrane. Using a mouse model for allergic contact dermatitis, we demonstrated that reduced migration of Ezh2-deficient LCs to the skin-draining lymph nodes resulted in the development of an exaggerated contact hypersensitivity (CHS) response despite tolerization with low dosage of an innocuous hapten 2, 4- dinitrothiocyanobenzene. Such breakdown in skin tolerance arises from the compromised activation of regulatory T cells, which consequently promotes an enhanced CD8+ T cell response in the sensitization phase of CHS. In addition, DC-intrinsic expression of Ezh2 was found to regulate early T cell developmental program particularly in adult mice. Deficiency of Ezh2 in thymic DCs favours the T cell lineage and leads to a profound developmental block characterized by a decrease in DP thymocytes, indicating their roles in directing lineage choices and DN thymocyte development. These developmental defects are accompanied by a change in the cytokine milieu of the thymus, suggesting the importance of DC-intrinsic Ezh2 in sustaining a proper thymic cytokine environment for normal T cell development. Collectively, our data highlighted the importance of Ezh2 in LCs for the regulation of their integrin-dependent migration, and also in thymic DCs for the maintenance of adult-stage early T cell development.